2010
DOI: 10.1128/jvi.02184-09
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Human Monoclonal Antibodies Neutralize both 1918 and 2009 Pandemic Influenza A (H1N1) Viruses

Abstract: The 2009 pandemic influenza A (H1N1) virus exhibits hemagglutinin protein sequence homology with the 1918 pandemic influenza virus. We found that human monoclonal antibodies recognized the Sa antigenic site on the head domains of both 1918 and 2009 hemagglutinins, a site that is hypervariable due to immune selection. These antibodies exhibited high potency against the 2009 virus in vitro, and one exerted a marked therapeutic effect in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
96
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 18 publications
(20 reference statements)
10
96
1
Order By: Relevance
“…Upon pH1N1 antigen stimulation, the memory B cell response produces cross-reactive antibodies against HAs of a number of different influenza virus strains. These results are consistent with the presence of plasmablasts secreting cross-reactive neutralizing antibodies in patients infected with pH1N1 (11,25,26,28,(38)(39)(40) and are in agreement with the hypothesis that pH1N1 infection may activate pre-existing memory B cells targeting conserved regions of HA molecule (12,13).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Upon pH1N1 antigen stimulation, the memory B cell response produces cross-reactive antibodies against HAs of a number of different influenza virus strains. These results are consistent with the presence of plasmablasts secreting cross-reactive neutralizing antibodies in patients infected with pH1N1 (11,25,26,28,(38)(39)(40) and are in agreement with the hypothesis that pH1N1 infection may activate pre-existing memory B cells targeting conserved regions of HA molecule (12,13).…”
Section: Discussionsupporting
confidence: 79%
“…However, limited data exist on the development and function of such memory B cells in humans. Recent studies using monoclonal antibodies from B cells isolated from patients infected with either the 1918 or 2009 pandemic H1N1 viruses suggest the presence of memory B cells (25)(26)(27). It was also reported that some HA-specific monoclonal antibodies isolated from these patients were cross-reactive with the stalk regions of HAs of a number of different influenza virus strains (13,28).…”
mentioning
confidence: 99%
“…Monoclonal antibodies derived from survivors of the 1918 pandemic were able to cross-neutralize 2009 H1N1 viruses (8). Exposure of animals to 1918-like viruses elicited antibodies that recognized novel H1N1 influenza isolates, whereas no antibody cross-reactivity or protection was observed following infection with contemporary seasonal influenza viruses (9,10).…”
mentioning
confidence: 98%
“…In conclusion, MAb 5J8 helps paint a more detailed picture of why older human subjects possessed 2009 H1N1 cross-reactive HA antibodies prior to exposure to the 2009 H1N1 virus (2, 9, 10), since epitopes other than the Sa site (11,13,19,22) or stem epitopes (6,8,17,18,21) contributed to this cross-protective effect. The relative importance of these epitopes for the antiviral humoral response may vary from person to person.…”
mentioning
confidence: 99%
“…Elderly people had preexisting antibodies against the 2009 virus (2, 9, 10). We and others have shown that the conservation of 1918-like sequences in the Sa antigenic site in the globular head domain of 2009 virus hemagglutinin (HA) is a likely structural correlate for this cross-reactivity (11,13,19,22). Sequence conservation, including the absence of glycosylation in early-20th-century strains and again in 2009 H1N1 virus HA, make this area on the HA protein surface an important target for human humoral immunity (19,22).…”
mentioning
confidence: 99%